The girls of Atomic City : the untold story of the women who helped win World War II - Kiernan, Denise (Simon & Schuster, 2013)
In this book the author traces the story of the unsung World War II workers in Oak Ridge, Tennessee through interviews with dozens of surviving women and other Oak Ridge residents. This is the story of the young women of Oak Ridge, Tennessee, who unwittingly played a crucial role in one of the most significant moments in U.S. history. The Tennessee town of Oak Ridge was created from scratch in 1942. One of the Manhattan Project's secret cities, it did not appear on any maps until 1949, and yet at the height of World War II it was using more electricity than New York City and was home to more than 75,000 people, many of them young women recruited from small towns across the South. Their jobs were shrouded in mystery, but they were buoyed by a sense of shared purpose, close friendships, and a surplus of handsome scientists and Army men. But against this wartime backdrop, a darker story was unfolding. The penalty for talking about their work, even the most innocuous details, was job loss and eviction. One woman was recruited to spy on her coworkers. They all knew something big was happening at Oak Ridge, but few could piece together the true nature of their work until the bomb "Little Boy" was dropped over Hiroshima, Japan, and the secret was out. The shocking revelation: the residents of Oak Ridge were enriching uranium for the atomic bomb. Though the young women originally believed they would leave Oak Ridge after the war, many met husbands there, made lifelong friends, and still call the seventy-year-old town home. The reverberations from their work there, work they did not fully understand at the time, are still being felt today.